Prospects for using wastewater from a farm for algae cultivation: The case of Eastern Colombia (2021)
: In recent years, the technical and economic feasibility of using microalgae and cyanobacteria has been explored for the removal and exploitation of domestic, agricultural and industrial residual effluents with high C, N and P compounds content. To contribute to the understanding of the process and its technical viability for microalgae growth, the article discusses monitoring, flow determination, and physicochemical characteristics of two types of effluents generated in an experimental farm located in the east of Colombia, before (R1) and after biological treatment (R2). In general, the results showed the reduction of different parameters, such as total dissolved solids (TDS), hardness, salinity and phosphates after treatment with activated sludge. However, the conductivity value obtained in R1 and R2 showed the presence of a pollutant load. These findings can be attributed to the highest concentration of fats and oils in the water during early hours of the day. Finally, although the concentration of nitrates increased from 46.63 to 225.21 mg∙dm–3 and phosphate decreased slightly from 9.65 to 6.21 mg∙dm–3, no inhibition was generated in the microalgae, as evidenced in the growth of the microalgal biomass in effluents after nitrate and phosphate removal above 80%.